Workplace Sexual Harassment Among Healthcare Workers: A Systematic Review of Antecedents and Consequences - Eka Fitriyani; Nurul Ain Hidayah Binti Abas (Psikobuletin:Buletin Ilmiah Psikologi, 2026)
Workplace sexual harassment (WSH) remains a "tip of the iceberg" phenomenon within the global healthcare sector, characterized by underreporting and a lack of systemic understanding.Objective: This systematic literature review (SLR) aims to identify the antecedents and consequences of WSH among healthcare professionals to inform policy and intervention strategies. Methods: Following PRISMA guidelines, a systematic search was conducted across five major databases (Scopus, SAGE, Springer, Wiley, and Science Direct) for peer-reviewed articles published between 2018 and 2024. A total of 21 studies met the inclusion criteria and were synthesized qualitatively. Results: Findings indicate that WSH manifests through three primary dimensions: gender harassment, unwanted sexual attention, and sexual coercion. Key antecedents include traditional gender roles and permissive organizational climates. Consequences are twofold, impacting individual psychological well-being (e.g., PTSD, anxiety) and organizational outcomes (e.g., high turnover, absenteeism). Conclusion: Addressing the hierarchical and gendered nature of healthcare environments is essential to mitigating the prevalence and deleterious effects of WSH.